2019
DOI: 10.1016/j.canlet.2019.03.048
|View full text |Cite
|
Sign up to set email alerts
|

Partnering with PARP inhibitors in acute myeloid leukemia with FLT3-ITD

Abstract: Internal tandem duplications within the juxtamembrane domain of fms-like tyrosine kinase 3 (FLT3-ITD) occur in acute myeloid leukemia (AML) cells of 20-25% of patients and are associated with poor treatment outcomes. FLT3 inhibitors have been developed, but have had limited clinical efficacy due to development of resistance, highlighting the need for better understanding of the function of FLT3-ITD and how to target it more effectively using novel combination strategies. Poly (ADP-ribose) polymerase (PARP) inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
2
8
0
Order By: Relevance
“…These results are consistent with those of our previous study, in which we demonstrated that the inhibition of STAT5 downregulates DNA repair [11]. Previous studies suggested that AML with genomic instability is sensitive to PARP inhibition [10,20]. Our results showed that the combination of 7c and olaparib synergistically inhibited FLT3-ITD + AML cells, revealing that an FLT3 inhibitor and a PARP inhibitor could be a promising therapeutic approach for FLT3-ITD + AML.…”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with those of our previous study, in which we demonstrated that the inhibition of STAT5 downregulates DNA repair [11]. Previous studies suggested that AML with genomic instability is sensitive to PARP inhibition [10,20]. Our results showed that the combination of 7c and olaparib synergistically inhibited FLT3-ITD + AML cells, revealing that an FLT3 inhibitor and a PARP inhibitor could be a promising therapeutic approach for FLT3-ITD + AML.…”
Section: Discussionsupporting
confidence: 93%
“…4D) that is a well-known prognostic marker associated with poor survival in ~25% of AML cases (Stirewalt and Radich, 2003). Our results further support the application of PARP inhibitors in FLT3 mutated AML, particularly in combination with synthetic lethal partners such as specific genetic alterations (Dellomo et al, 2019). Surprisingly, our results revealed that abnormally low expression of PARP1 in FLT3-ITD negative AML (~75% of cases) is associated with poor survival (Fig.…”
Section: Discussionsupporting
confidence: 81%
“…Hyperactivation of PARP pathway observed in tumors can be used to selectively kill tumor cells. PARPi treatment was shown to be effective in monotherapy and in combination therapies mainly in gynecological cancers, and researchers also suspect potential of PARP inhibitors involvement in acute myeloid leukemia [9,12,13].…”
Section: Introductionmentioning
confidence: 99%